Transient Neonatal Diabetes, ZFP57, and Hypomethylation of Multiple Imprinted Loci: A detailed follow-up - Boonen, Susanne E. (American Diabetes Association, 2013)
OBJECTIVE: Transient neonatal diabetes mellitus 1 (TNDM1) is the most common cause of diabetes presenting at birth. Approximately 5% of the cases are due to recessive ZFP57 mutations, causing hypomethylation at the TNDM locus and other imprinted loci (HIL). This has consequences for patient care because it has impact on the phenotype and recurrence risk for families. We have determined the genotype, phenotype, and epigenotype of the first 10 families to alert health professionals to this newly described genetic subgroup of diabetes. RESEARCH DESIGN AND METHODS: The 10 families (14 homozygous/compound heterozygous individuals) with ZFP57 mutations were ascertained through TNDM1 diagnostic testing. ZFP57 was sequenced in probands and their relatives, and the methylation levels at multiple maternally and paternally imprinted loci were determined. Medical and family histories were obtained, and clinical examination was performed. RESULTS: The key clinical features in probands were transient neonatal diabetes, intrauterine growth retardation, macroglossia, heart defects, and developmental delay. However, the finding of two homozygous relatives without diabetes and normal intelligence showed that the phenotype could be very variable. The epigenotype always included total loss of methylation at the TNDM1 locus and reproducible combinations of differential hypomethylation at other maternally imprinted loci, including tissue mosaicism. CONCLUSIONS: There is yet no clear genotype–epigenotype–phenotype correlation to explain the variable clinical presentation, and this results in difficulties predicting the prognosis of affected individuals. However, many cases have a more severe phenotype than seen in other causes of TNDM1. Further cases and global epigenetic testing are needed to clarify this.